2022
DOI: 10.3390/diagnostics12112608
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Noninvasive Diagnostic Tests for the Detection of Significant and Advanced Fibrosis Stages in Nonalcoholic Fatty Liver Disease: A Systematic Literature Review of the US Studies

Abstract: Background: The purpose of this systematic literature review (SLR) was to evaluate the accuracy of noninvasive diagnostic tools in detecting significant or advanced (F2/F3) fibrosis among patients with nonalcoholic fatty liver (NAFL) in the US healthcare context. Methods: The SLR was conducted in PubMed and Web of Science, with an additional hand search of public domains and citations, in line with the PRISMA statement. The study included US-based original research on diagnostic test sensitivity, specificity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
2
2
0
1
Order By: Relevance
“…The accuracy analysis showed that both threshold values for liver fibrosis assessment (manufacturer and ROC-derived) are characterized by high NPV values (91-98%), but lower PPV values, which was also observed by others [44,45]. We also found that the PPV values were higher for ROC-derived cut-offs and that using these threshold values gives fewer false positive results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The accuracy analysis showed that both threshold values for liver fibrosis assessment (manufacturer and ROC-derived) are characterized by high NPV values (91-98%), but lower PPV values, which was also observed by others [44,45]. We also found that the PPV values were higher for ROC-derived cut-offs and that using these threshold values gives fewer false positive results.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we noted that the highest concordance rates (FIB-4/TE vs. FIB-4/LFRI) were shown for results indicating a low ALF risk, which may suggest that the second-level non-invasive tests, such as TE or LFRI, are more consistent in the low-risk assessment for excluding ALF, even in patients with MAFLD. On the contrary, the concordance rates in the intermediate- and high-risk categories were lower, which indirectly supports the recommendation that ALF risk in these groups should be verified by liver biopsy [ 9 , 45 , 46 ]. It should be mentioned that TE may have some limitations and may overestimate the risk of ALF, especially in obese individuals.…”
Section: Discussionsupporting
confidence: 71%
“…These findings highlight the limitations of solely focusing on advanced fibrosis while broadening the scope of CVD risk assessments in MASLD. While FIB-4 < 1.3 and NFS < -1.455 demonstrate good performance in excluding advanced fibrosis [116,117] , aligning with the primary goal of current guidelines for fibrosis assessment in the MASLD population, they exhibit relatively poor performance in ruling out significant fibrosis [117][118][119] . This presents a notable challenge, with special reference to patients classified as low-risk, who represent up to 80% of individuals with MASLD [120] .…”
Section: New Evidence: Emphasis On Liver-related Parameters and Oppor...mentioning
confidence: 82%
“…These tests and their algorithms should be tested prospectively for their ability to predict outcomes and be cost-effective. 6 Until then, we do agree with the major guidelines and continue to suggest the use of the FIB-4 score as the first line NIT for risk stratification.…”
mentioning
confidence: 76%